Magneto-Optical properties of noble-metal nanostructures: functional nanomaterials for bio sensing - Maria Grazia Manera (Nature Portfolio, 2018)
Abstract Metallic nanostructures supporting Localized Surface Plasmon Resonances (LSPR) are characterized by their unique ability to control and manipulate light at the nanoscale. Noble metal nanostructures, such as gold nanostructures, are demonstrating to exhibit magneto-optic activity in the presence of modulated magnetic field of low intensity in transversal configuration (T-MOKE). Validation of experimental findings was achieved by numerical simulations based on Finite Element Method (FEM) techniques. The developed numerical models allowed studying the combination of the T-MOKE effect with the localized surface plasmon resonance of metal nanoparticles. Numerical optical and magneto-optical spectra provided a deep insight on the physical aspects behind the magneto-optical activity of metal nanostructures strictly related to direction of oscillations electrical dipoles generated in resonance conditions. Additionally the MO signal was characterized as a transducing signal for refractive index sensing in liquid conditions. The outcome is an increase in the limit of detection of magneto optical transducer with respect to traditional plasmonic sensors. A new strategy for magneto-plasmonic sensing based on the use of glass supported -Au nanostructures based on their MO properties has put forward.